Cortisol effects on autobiographic memory retrieval in PTSD: an analysis of word valence and time until retrieval. (September 2013) - Wingenfeld, Katja; Driessen, Martin; Schlosser, Nicole; Terfehr, Kirsten; Carvalho Fernando, Silvia; Wolf, Oliver Tobias
Abstract In healthy participants, cortisol administration has been found to impair autobiographic memory retrieval. We recently reported that administration of 10 mg of hydrocortisone had enhancing effects on autobiographical memory retrieval, i.e. more specific memory retrieval, in patients with posttraumatic stress disorder (PTSD), while in healthy controls the impairing effects were replicated. We here report a re-analysis of these data with respect to cue-word valence and retrieval time. In a placebo-controlled cross-over study, 43 patients with PTSD and 43 age- and sex-matched healthy controls received either placebo or hydrocortisone orally before the autobiographical memory test was performed. We found that the effects of cortisol on memory retrieval depended on cue-word valence and group (significant interaction effects of drug by group and drug by valence by group). The enhancing effect of cortisol on memory retrieval in PTSD seemed to be relatively independent of cue-word valence, while in the control group the impairing effects of cortisol were only seen in response to neutral cue-words. The second result of the study was that in patients as well as in controls, cortisol administration led to faster memory retrieval compared to placebo. This was seen in response to positive and (to lesser extend) to neutral cue-words, but not in response to negative cue-words. Our findings illustrate that the opposing effects of cortisol on autobiographical memory retrieval in PTSD patients and controls are further modulated by the emotionality of the cue-words.